The Moderating Effect of Personality on the Relationship Between Objectively Measured Physical Activity and Depression and Anxiety Among Adolescents: Results From the Tromsø Study – Fit Futures - Hembre, Martine Helgesen; Håkonsen, Ellen Asplund (UiT Norges arktiske universitet, 2019)
The purpose of this study was to examine the relationships between physical activity, personality and mental distress in an adolescent sample. We also investigated if the relationship between physical activity and mental distress is dependent on personality. Analyses were based on data from the second wave of the Tromsø study – Fit Futures. An objective measure of physical activity was used, in addition to self reports on physical activity, mental distress, and personality. 366 participants (233 female and 133 male) were included in the analyses (Mage = 18.52, SD = 1.75). Separate multiple hierarchical regression analyses were conducted for each personality trait to determine whether the trait had a moderating effect on the relationship between physical activity and depression. Results identified a possible negative interaction between steps per day and low scores on Neuroticism. A negative interaction between steps per day and high scores on Conscientiousness was also found. However, the results were uncertain and this was discussed. Because personality is fluctuating, and because many factors may contribute to the effect of physical activity, further research using objective measures are needed. Conclusions: Our results indicated that physical activity was not related to mental distress, except perhaps for participants low in Neuroticism and high in Conscientiousness.